(untitled) - Axilrod, S. H (Oxford, 2013)
This book aims to clarify for a broad public audience what the federal reserve system, the nation's central bank, does, while still being of interest to former colleagues and others who study and evaluate its practices
Keywords: Monetary policy,Ngân hàng dự trữ liên bang,Chính sách tiền tệ,Chính sách kinh tế,Federal Reserve banks; Economic policy,Hoa Kỳ; United States,United States,Hoa Kỳ